The Students' Autonomous English Learning Using Technology-Enhanced Language Learning Tools in Seven-Grade of SMP Telkom Purwokerto - Ghaida Thifal; Muflihah - (Program Studi Diploma Tiga Bahasa Inggris Fakultas Ilmu Budaya Unsoed, 2025)
This research aimed to describe how the 7th grade students of SMP Telkom Purwokerto used TELL tools in autonomous English learning and to explain the advantages as well as the challenges of using it. This study used a descriptive qualitative approach. The data collection techniques used were observation, interview, and documentation. The data analysis techniques used refer to John W. Creswell, which includes organizing and preparing the data, reading and reviewing the data, coding the data, generating themes, and representing the description and themes. With the development of integration technology in education, TELL tools including online platforms, mobile applications, and digital resources have changed the way students learn English autonomously. This research found that the students use some TELL tools namely Roblox, Instagram, TikTok, YouTube, Google, and Duolingo. The students used the tools to see and watch some English learning and random English videos. They also used it to help them practice their English by engaging in games or interacting with other people. It helps them gain new knowledge about English and how to use it in their daily lives. Using TELL tools in autonomous learning has some other advantages such as being affordable, convenient and flexible, and offering more personalized learning. The findings also reveal that students face several challenges in the process. These challenges include difficulties in maintaining motivation, an overwhelming abundance of resources, a lack of feedback, and dealing with difficult topics.